دور الامام المغيلي التلمساني في نشر المذهب المالكي - ايمان العسلي; سمية قضباني; د/ نورالدين صغيري (جامعة عمار ثليجي الاغواط, 2016)
اﻟﻤﻠﺨﺺ ﺑﺎﻟﻌﺮﺑﻴﺔ : إن التطورات الﱵ حدثت لبﻼدنا، اية القرن 15م ﺑﺪاﻳﺔ اﻟﻘﺮن 16م كانت خطﲑة، وقد مست ﺟﻮاﻧﺐ اﳊﻴﺎة اﻟﺴﻴﺎﺳﻴﺔ واﻻﺟﺘﻤﺎﻋﻴﺔ ﻟﻠشعوب اﻹسﻼمية، لكن ﱂ يكن ﳍذه التطورات تأثﲑ على الناحية الثقافية والعلمية، ﳌا عرفته من حركة واسعة ﰲ هذا اال، وقد برز ﰲ تلك الفﱰة، ﳔبة من العلماء الذين بصموا على سجل التاريخ اﻹسﻼمي بصمة غائرة، وكان من بينهم اﻹمام ﳏمد بن عبد الكرﱘ اﳌغيلي اﻟﺬي عمل ﲟبدإ اﻷمر باﳌعروف والنهي عن اﳌنكر، قوﻻ وعمﻼ، وكان ﳍذا الرجل جانب إصﻼحي دعوي خﻼل الرحﻼت الﱵ قام ا آنذاك، وقد اشتهر بفتواه ﰲ نازلة يهود توات، وبرز فيها اﻹمام برأي خالفه فيه بعض الفقهاء، لكن هناك من وافقه وأيّده على ذلك، وقد امتدت رحﻼت اﻹﻣﺎم إﱃ إﻓﺮﻳﻘﻴﺎ اﻟﻐﺮﺑﻴﺔ وﲡﻮل ﺑﲔ ﻣﻠﻮﻛﻬﺎ وأﻣﺮاﺋﻬﺎ ﻣﺼﻠﺤﺎ وﻧﺎﺷﺮا ﻟﻠﺪﻳﻦ اﻹﺳﻼﻣﻲ ﻋﺎﻣﺔ واﳌﺬﻫﺐ اﳌﺎﻟﻜﻲ ﺧﺎﺻﺔ وﺗﺮك ﻫﺬا اﻟﻌﺎﱂ اﳉﻠﻴﻞ آﺛﺎرا ﻋﻠﻤﻴﺔ ﻣﻨﻬﺎ ﻣﺎﻫﻮ ﳏﻘﻖ وﻣﻨﻬﺎ ﻣﺎﻫﻮ ﰲ ﺧﺰاﻧﺎت اﻟﺰواﻳﺎ واﳌﺪارس اﻟﻘﺮآﻧﻴﺔ ﳛﺘﺎج إﱃ ﺑﺎﺣﺚ ﻳﻌﻴﺪ دراﺳﺘﻪ وﻛﺘﺎﺑﺘﻪ ﻣﻦ ﺟﺪﻳﺪ ﻟﺘﻌﻢ اﻟﻔﺎﺋﺪة اﻟﱵ ﺗﺮﻛﻬﺎ ﻟﻨﺎ اﻹﻣﺎم واﻟﻌﺎﱂ اﳌﻐﻴﻠﻲ اﻟﺘﻠﻤﺴﺎﱐ .ﻫﺬا وﻧﺮﺟﻮا أن ﻧﻜﻮن ﻗﺪ وﻓﻘﻨﺎ ﰲ إيصال ما كنا نرمي إليه، وان تكون عثراتنا معدودة، واﷲ من وراء القصد . اﻟﻤﻠﺨﺺ ﺑﺎﻹﻧﺠﻠﻴﺰﻳﺔ: The developments that have taken place in our the country by the end of 15 th and the beginning of the 16 th was and compassed Islamic people life ‘s aspects social, political …But these developments did not influence the cultural and scientific domain, even it was too broad Also Has been featured in that period, a group of scholars who thumb printed on Islamic history record imprint bygone. Among them was the leader “Imam” Muhammad bin Abdul Karim Maghili operating principle of enjoining what is right and forbidding of evil in word and deed, and this man had an Islamist reconciliation and call, during the trips he has made at that time. He was famous by his verdict in coming down of -Jews of Toit, And it emerged forward view which is against some jurisprudents, but there were other group who supporting him, Imam’s trips who extended to West Africa and wander among their kings and princes, as a reformer and publisher of the Islamic religion in general and Maliki School especially, This big learner leaved scientific traces, some are writing and some still in the corners cupboard and Koranic schools, need a researcher to re-examine and writing again to learn the interest bequeathed to us by the front and the leader Maghili Tlemceni. Finally , and we hope that we accomplished the mission successfully, in transmitting all what we desire and wish and our mistakes and nonsense be less
منطقة توات انموذجا